Atrial Myxoma: histological Confirmation - Ngow, Harris Abdullah; Wan Mohd Nowalid, Wan Khairina (The Journal of the Asia Pacific Heart Association, BMJ Publishing, 2011)
Atrial myxoma is uncommon, with an overall prevalence in the developed world of 0.02%.1 It is often undiagnosed until complications such as cardiac death or stroke occur. The incidence of primitive tumours of the heart at autopsy is between 0.0017% and 0.03%, and of these 50% are myxomas. 12 We describe a case of left atrial myxoma which was only diagnosed after histopathological examination.